Surface Phytoplankton Assemblages and Controlling Factors in the Strait of Malacca and Sunda Shelf - Liu, Haijiao; Wu, Chao; Xu, Wenzhe; Wang, Xingzhou; Thangaraj, Satheeswaran; Zhang, Guicheng; Zhang, Xiaodong; Zhao, Yuying; Sun, Jun (Frontiers in Marine Science, 2020)
Shifts in phytoplankton phenology were observed in the Strait of Malacca (SM) and Sunda Shelf (SS), which were speculated to be potentially related to global warming and climate anomaly events. Such interactions between phytoplankton structure and physico-chemical factors were less known in narrow straits. Therefore, the spatial distribution pattern and diversity of surface phytoplankton assemblage, local hydrology, and nutrient regimes were investigated over the SM and SS (South China Sea, SCS) during 2017 and 2018 pre-monsoon season (spring). Diatoms, dinoflagellates, and cyanobacteria were representatives of microphytoplankton in the survey area. Total phytoplankton abundance peaked near Singapore Strait (SGS) and diminished toward SS. From the lower ratio of diatoms to dinoflagellates (<3) in SS, we deduced lower carbon pump efficiency here. In agreement with the modeled results proposed previously, cold conditions (negative Indian Ocean Dipole, IOD) were more suitable for high diatom (especially centric forms) abundance, while warm scenarios (positive IOD/El Niño period as in 2017) seemed to favor dinoflagellates and/or cyanobacteria. Specifically, diatom proportion increased by 30% and dinoflagellate, cyanobacteria reduced by 71%, 75% in response to shifts of climate anomaly from 2017 cruise to 2018 cruise. This study between field microalgae and physical and chemical conditions would be helpful to launch large-scale climate model, biogeochemistry, and carbon cycling in future research.